Integrated Physiological and Metabolomic Analyses Reveal the Differences in the Fruit Quality of the Blueberry Cultivated in Three Soilless Substrates - Haiyan Yang; Yongkang Duan; Zhiwen Wei; Yaqiong Wu; Chunhong Zhang; Wenlong Wu; Lianfei Lyu; Weilin Li (Foods, 2022)
With improving living standards, traditional blueberry planting modes cannot meet commercial demands, and blueberry cultivation with soilless substrate has become a popular solution in the blueberry industry. In this study, different soilless substrate treatments were found to markedly influence fruit appearance and intrinsic quality. The fruit in the 50:50 peat/pine bark (v/v) (FPB) treatment group had the maximum single fruit weight, largest vertical diameter, and brightest color, as well as the highest 1,1-diphenyl-2-picrylhydrazyl (DPPH) value, solid-acid ratio and anthocyanin content. The fruit in the 50:50 pine bark/rice husk (v/v) (FBR) treatment group had the highest total phenol and flavonoid levels, largest drip loss value, and lowest total pectin content and firmness value. Metabolomic analysis showed that flavonoid, carbohydrate, and carbohydrate conjugate, and amino acid, peptide, and analog levels were significantly different between groups. Fruit in the FPB group had the highest sucrose, D-fructose 1,6-bisphosphate, salidroside, tectorigenin, naringenin chalcone, trifolirhizin, and galangin contents. The increase in the relative expression of phenylalanine (Phe) promoted the synthesis of fruit polyphenols in the FBR group. Our results provide new insights into the effects of different substrates on the quality of blueberries and a reference for the soilless substrate cultivation of blueberries.